PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI PERTUMBUHAN DAN PEMBANGUNAN EKONOMI - Telaumbanua, Karius (LPPM Universitas Nias Raya, 2024)
This Classroom Action Research aims to evaluate the improvement of learning outcomes in the Economic Growth subject among students of grade XI-IPS at SMA Negeri 2 Toma through the implementation of Problem Based Learning. The research method employed is classroom action research, which involves a series of stages from planning, implementation, observation, reflection, recommendations, to the evaluation of students' learning outcomes. The research findings indicate that students' activities in implementing the stages of the Problem Based Learning model in the economics subject, particularly in understanding the Concepts and Factors of Economic Growth, experienced a significant improvement, reaching over 75%. This improvement is also reflected in the number of students who successfully achieved the Minimum Completeness Criteria (KKM), which increased by 25.16%. Additionally, the average learning outcomes of students increased from 69.89 in Cycle I to 80.89 in Cycle II. Furthermore, students' responses and attitudes towards the implementation of the Problem Based Learning model were highly positive, demonstrating the effectiveness of the model in enhancing the quality of learning.